KAWASAN EKONOMI KHUSUS (KEK) MANDALIKA DALAM IMPLEMENTASI KONSEP PARIWISATA BERBASIS ECOTOURISM: PELUANG DAN TANTANGAN - E, Heavy Nala (Mandala: Jurnal Ilmu Hubungan Internasional, 2019)
This article analyzes the concept of ecotourism as an alternative to the eco-friendly tourism sector. The tourism sector becomes one of the strategic sectors in increasing the country's economic growth. The multiplier effect of tourism industry makes this sector continue to increase significantly. Indonesia sets this sector as core leading sector. The government's seriousness in working on tourism destinations, realized by forming Special Economic Zone (KEK) of tourism, one of which is KEK Mandalika. However, in the midst of mass tourism development, the concern over environmental issues has come under scrutiny. Tourism industry demanded to also pay attention to the environmental damages caused by the development of the tourism industry. This research further finds that KEK Mandalika uses the ecotourism concept in response to the demands for the tourism industry to be sustainable and started to put more concern over environmental issues. The application of ecotourism in several sectors in KEK Mandalika is done because ecotourism is called to be an alternative for the development of eco-friendly tourism sector. However, a number of challenges arise on how ecotourism should not only involves a small part of the entourage or elite party, and still put forward the environmental aspect amid the demands of a rapidly growing tourism market.